FORMULASI GEL HAND SANITIZER EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Prayoga, Tria; Agustina, Ika; Lisnawati, Nia; Robby, Rohima; Hidayah, Nurul (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
In an effort to counteract skin irritation due to repeated use of alcohol-based hand sanitizers, there is increasing interest in non-alcoholic alternatives incorporating natural antibacterial ingredients. This study focuses on developing a hand sanitizer gel utilizing ethanol extract from Averrhoa bilimbi L. leaves as an antibacterial agent, evaluating the effect of Carbopol 940 concentration on product characteristics. The aimed to develop a hand sanitizer gel that leverages the antibacterial properties of Averrhoa bilimbi L. leaf ethanol extract, by testing the effects of different Carbopol 940 concentrations (0.4%, 0.5%, and 0.6%) on product characteristics. The methods used included organoleptic, homogeneity, viscosity, and pH tests, with data processing using one-way ANOVA and Tukey HSD. Tye results of Organoleptic and homogeneity testing of all gel formulas on a weekly basis revealed consistent characteristics, with a yellow-brown color and a distinctive aroma characteristic of the Averrhoa bilimbi L. leaf extract. Furthermore, results showed that viscosity increased with the concentration of Carbopol 940, with the 0.6% formulation achieving the highest stability. However, all formulations had a pH range of 6.49 to 6.85, above the ideal skin range of 4.5–6.5. Quantitatively, significant differences in viscosity among the formulations were observed, while pH variations were not significant. The conclusion of the study confirmed that the Carbopol 940 concentration significantly affect viscosity, but further adjustments are needed to optimize the gel's pH to meet skin standards and enhance efficacy as a hygiene product.